Emergency power supply monitoring and testing embedded in transfer switches - Kukkurainen, Martti (My University, 2017)
In this thesis, the key components of the emergency power supply system (EPSS) and the extended scope of critical power standards are reviewed and discussed by strongly emphasizing the facility manager’s perspective, operating in hospitals and datacentres. Furthermore, the established industry practices and major challenges experienced by the facility manager in terms of operational testing and routine maintenance were identified and analysed in order to create a space for further research. The emergency supply equipment, e.g., the emergency diesel generator (EDG) and specifically automatic transfer switches (ATS) were selected as the key areas for further investigation. The purpose of the thesis was to explore the NFPA 110, Standard for Emergency and Standby Power Systems, and deeply understand the variety of the mandatory requirements and compare them to the actual operating conditions and practices. The research was performed using industry regulations, maintenance procedures, white papers, and articles written by the industry specialist as a source of information. Based on the research, the final target was to identify the specific operating practices and standard requirements that could be automatically executed by adding new embedded features and functionalities to the automatic transfer switches. As a conclusion, the following areas were identified: automated condition monitoring, automated test sequence including test data collection, system performance monitoring and trending tools. Therefore, the main recommendation was that the ATS equipment with embedded features shall become a key interface between the emergency power supply system and the facility manager. The goal was to clarify the roles and responsibilities between stakeholders and increase the efficiency of the maintenance and testing work.
Keywords: emergency power supply; generating set; transfer switch; fi=Energiatekniikka|en=Energy Technology|; fi=Sähkö- ja energiatekniikan koulutusohjelma (DI)|